Screening of selected Malaysian plants against several food borne pathogen bacteria - Abd Aziz, S. M.; Low, C. N.; Chai, L. C.; Abd Razak, S. S. N.; Selamat, Jinap; Song, Jason; Sarker, Md. Zaidul Islam; Khatib, Alfi (Universiti Putra Malaysia, 2011)
This study was conducted to evaluate antimicrobial properties of ethanolic extracts of the leaves of Nephelium lappaceum, Curcuma longa, Cinnamomun cassia, Durio zibethinus, Vitex trifolia, Amaranthus tricolor, Syzygium samarangense and Manihot esculenta. Antibacterial properties of the extracts were studied against fifteen strains of different gram positive and gram negative pathogenic bacteria, including Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, Vibrio para, and Escherichia coli using the agar disk diffusion method. Among the tested extracts, only Amaranthus tricolor exhibited specific inhibition of one of the tested bacteria; Bacillus cereus. Using the microdilution method, its minimum inhibitory concentration (MIC) value was determined to be 20 mg/mL.